Advances in Experimental Medicine and Biology: Intrafascicular Local Anesthetic Injection Damages Peripheral Nerve-Induced Neuropathic Pain - Tseng, Kuang-Yi; Wang, Hung-Chen; Chang, Lin-Li; Cheng, Kuang-I (Advances in experimental medicine and biology, 2018)
Peripheral nerve blockade (PNB) is advantageous for patients undergoing surgery to decrease the perioperative opioid consumptions and enhance recovery after surgery.Inadvertent local anesthetic (LA) administration into nerve fiber intrafascicularly easily results in unrecognized nerve injury. Using nerve block guidance either by ultrasound, electrical nerve stimulator, or using pressure devices does not prevent nerve damage, even though most of the nerve injury is transiently. The incidence of neurologic symptoms or neuropathy is in the range of 0.02-2.2%, and no significant difference of postoperative neurologic symptoms is found as compared with using ultrasound or guided nerve stimulator technique. However, intrafascicular lidocaine brought about macrophage migration into the damaged fascicle, Schwann cell proliferation, increased intensity of myelin basic protein, and shorten withdrawal time to mechanical stimuli. In dorsal root ganglion (DRG), intrafascicular LA injection increased the activated transcriptional factor 3 (ATF-3) and downregulated Nav1.8 (Nav1.8). In spinal dorsal horn (SDH), the microglia and astrocytes located in SDH were activated and proliferated after intrafascicular LA injection and returned to baseline gradually at the end of the month. This is a kind of neuropathic pain, so low injection pressure should be maintained, the correct needle bevel used, nerve stimulator or ultrasound guidance applied, and careful and deliberately slow injection employed as important parts of the injection technique to prevent intrafascicular LA administration-induced neuropathic pain.